Nanotubular hard carbon derived from renewable natural seed gel for high performance sodium-ion battery anode - Sharma, Neha; Gawli, Yogesh; Ahmad, Absar; Muhammed, Musthafa; Ogale, Satishchandra (Chemistryselect, 2017)
Electrical energy storage devices such as batteries and supercapacitors are perhaps the most researched topic today in view of its critical implications for the successful implementations of various renewable energy harvesting initiatives. Amongst the various battery systems being currently examined, the Li-battery continues to be a main player, but the Na-ion battery has been attracting significant attention lately due to the concerns about the limited reserves and high cost of Li. Hard carbon is recognized to be a good anode material for Na-battery. In this work we present a novel approach to synthesize such hard carbon from a natural gel derived from the commonly used Basil seeds (Osimum Basilicum) which swell 30 times their weight by absorbing water. The hard carbon obtained by pyrolysis of the freeze-dried mucilage possesses sheet-like and tubular morphology with decorated surface defects attributed to the presence of oxygen functionalities. This hard carbon shows a good reversible capacity of 195 mAh g(-1) at 0.1A g(-1) with an impressive approximate to 91% retention of initial capacity after 300 cycles and sustains high current densities with not much change in capacity value.